Brief Report: Impact of ART Classes on the Increasing Risk of Cerebral Small-Vessel Disease in Middle-Aged, Well-Controlled, cART-Treated, HIV-Infected Individuals. (15th August 2019) - Januel, Edouard; Godin, Ophelia; Moulignier, Antoine; Lescure, François-Xavier; Savatovsky, Julien; Lamirel, Cédric; Valin, Nadia; Tubiana, Roland; Canestri, Ana; Roux, Pascal; Sadik, Jean-Claude; Salomon, Laurence; et al.
Abstract : Background: Cerebral small-vessel disease (CSVD) is a chronic disease accounting for one-third of strokes and the second etiology of dementia. Despite sustained immunovirological control, CSVD prevalence is doubled in middle-aged persons living with HIV (PLHIVs), even after adjustment for traditional cardiovascular risk factors. We aimed to investigate whether exposure to any antiretroviral drug class could be associated with an increasing risk of CSVD. Methods: The MicroBREAK-2 case–control study (NCT02210130) enrolled PLHIVs aged 50 years and older, treated with combined antiretroviral therapy for ≥5 years, with plasma HIV load controlled for ≥12 months. Cases were PLHIVs with radiologically defined CSVD, and controls were CSVD-free PLHIVs matched for age (±5 years), sex, and year of HIV diagnosis (±5 years). Multivariable conditional logistic regression analyses focused on cumulative exposure to nucleoside reverse transcriptase inhibitors, non-nucleoside reverse transcriptase inhibitors, protease inhibitors and/or exposure to integrase inhibitors (yes or no), adjusted for hypertension, CD4 nadir, current CD4/CD8 ratio, and HIV transmission group. Results: Between May 2014 and April 2017, 77 cases and 77 controls (85.7% males) were recruited. PLHIVs' median age was 57.6 years, and median HIV diagnosis year was 1992. The increasing risk of CSVD was not associated with exposure to any ART class. Conclusion: No deleterious effect of ART class exposure on the risk of CSVD was found for middle-aged treated PLHIVs.